Cardinal Stefan Wyszyński on Universities and Philosophy - Bp. Jacek Grzybowski (Chrześcijaństwo-Świat-Polityka)
The article discusses the writings and speeches of the Polish Primate, Blessed Cardinal Stefan Wyszyński, on academic life. The article addresses the very idea of the university and academic work in service to the community. This topic has received scant attention so far.